Maritime Defence Empowerment in the Development of Fishermen's Communities in Sungsang Waters, Banyuasin Regency, South Sumatra - Zainubbi Zainubbi; Amin Rejo; Andries Lionardo; Muhammad Hendri Gumay (Dinasti International Journal of Education Management And Social Science, 2024)
According to Republic of Indonesia Law No. 34 of 2004 addressing the INAF, the duties of the Indonesian Navy are outlined in Article 9 paragraph (e): to implement Dawilhanla. Dawilhanla is the empowerment of coastal communities through Binpotmar, which is implemented by Lantamal III/JKT in Banyuasin regency, South Sumatra, coastal areas represented by Bungakarang Village, Tanjung Lago regency, Marga Sungsang, Sungsang I-IV, Pili Village, Banyuasin II regency. The purpose of organizing the Empowerment of Maritime Defense areas is: in the perspective of Hanneg's interests is to prepare maritime defense areas and support forces as early as possible to win the conflict. From a community perspective, it aims to assist in overcoming community challenges and improving the welfare of maritime communities. The purpose of this research is to analyze Lantamal/JKT's strategy for empowering marine defense areas to improve the welfare of fishing communities in Banyuasin regency, South Sumatra, as well as to develop a model of this strategy. The research employed a qualitative research approach. Data was collected from designated informants and analyzed using qualitative techniques. The findings of research on coastal community empowerment are limited by only providing assistance to fishermen, which is not optimal considering the limited budget. Synergy between agencies is not implemented in a sustainable manner that meets the needs of the fishing community. The conclusion of the implementation of the coastal community empowerment strategy to increase the income of coastal communities/fishermen in Banyuasin Regency, South Sumatra Province, was not successful.